(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract One of the major health threats in the world today, Mycobacterium tuberculosis (Tuberculosis or TB) has become even more problematic because of the development of the drug-resistant strains. It is essential to develop new therapeutics to fight this emerging problem. This paper will outline an in-silico design, growth and evaluation of a set of coumarin-thiazolidinone hybrids as possible inhibitors of M. tuberculosis. The X-ray crystallographic structure of the target protein (PDB ID: 7U0M) was used in molecular docking and the binding interactions of the compounds were evaluated with AutoDock Vina. Hydrophobic interaction, hydrogen bonding and 0-stacking were found to be significant interactions between the ligands and active site residues of the target protein. SK9 was selected as the most promising candidate out of the ten compounds analyzed because it had a strong binding affinity with the target protein and a high binding energy as compared to the co-crystal ligand. Simulations using molecular dynamics also provided the stability of SK9-protein complex, and the profiles of RMSD, RMSF, and radius of gyration were favourable, suggesting strong protein-ligand interactions. These findings were supported by the binding free energy analysis which is a MM-GBSA approach with SK9 displaying a better total binding energy than the co-crystal ligand. Despite the fact that this research is purely in-silico, promising outcomes give a basis to subsequent biological measurements. The in-vitro and in-vivo testing is needed to confirm the efficacy and safety of these compounds as their potential use as anti-TB agents. This study illustrates the strength of computer methods in identification of new TB inhibitors and preludes the formulation of new medicines against drug-resistant TB.